2021
DOI: 10.3390/ijerph18052384
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Dysfunction in Peripheral Artery Disease: Is Heat Therapy a Viable Treatment?

Abstract: Peripheral artery disease (PAD) is characterized by the development of atherosclerotic plaques in the lower-body conduit arteries. PAD is commonly accompanied by microvascular disease, which may result in poor wound healing, plantar ulcer development, and subsequent limb amputation. Understanding the mechanisms underlying the development of plantar ulcers is a critical step in the development of adequate treatment options for patients with PAD. Skin is classified into two major components: glabrous and non-gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 52 publications
0
14
0
10
Order By: Relevance
“…Laser speckle contrast imaging (LSCI) is a wide-field, noninvasive imaging technique with high temporal and spatial resolution, which is based on the analysis of light signals after scattering and random interference, and therefore obtains the velocity information of scattering particles in biological tissues (e.g., red blood cells) 1 . Conventionally, it works on the reflective-detected mode, and has been widely used in the fundamental research of microcirculation 2 7 , whose dysfunction is highly relevant to a series of clinical symptoms, such as diabetes 8 , ischemic stroke 9 , 10 , coronary heart disease 11 and peripheral artery disease 12 . With surgery-based open-skull windows, thinned-skull windows, and surgery-free skull optical clearing windows, cortical blood flow distribution could be clearly observed using conventional reflective-detected LSCI technique 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Laser speckle contrast imaging (LSCI) is a wide-field, noninvasive imaging technique with high temporal and spatial resolution, which is based on the analysis of light signals after scattering and random interference, and therefore obtains the velocity information of scattering particles in biological tissues (e.g., red blood cells) 1 . Conventionally, it works on the reflective-detected mode, and has been widely used in the fundamental research of microcirculation 2 7 , whose dysfunction is highly relevant to a series of clinical symptoms, such as diabetes 8 , ischemic stroke 9 , 10 , coronary heart disease 11 and peripheral artery disease 12 . With surgery-based open-skull windows, thinned-skull windows, and surgery-free skull optical clearing windows, cortical blood flow distribution could be clearly observed using conventional reflective-detected LSCI technique 13 .…”
Section: Introductionmentioning
confidence: 99%
“…They assessed the temperature change on the sole of the big toe in response to local heating. The researchers found that in people with PAD, the activity of the endothelium, smooth muscles and the nervous system during heating was significantly lower compared to healthy controls [ 4 ]. Heat therapy, which is the use of an external heat source to raise local or systemic body temperature, has proven to be an effective intervention in patients with PAD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In late-stage PAD, when tissue perfusion is no longer able to meet the metabolic demands of the tissues, critical limb ischemia can develop. This often leads to chronic ischemic pain, ulceration and eventually even amputation [ 3 , 4 ]. Patients are recommended to perform physical activity (i.e., walks lasting at least 30–45 min, walks 3 times a week) [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin necrosis occurs (Figure 26c, d). 16,[51][52][53] There is a discrepancy between the total microcirculation and the purely nutritive microcirculation due to a maldistribution of blood flow between nutritive and nonnutritive vessels in ischemic skin. While nutritive blood flow in PAD patients has been comparable to that of healthy subjects for some time, total blood flow, as measured at the capillary level by LDF, is increased in PAD patients compared to healthy subjects.…”
Section: Microcirculatory Disorders In Peripheral Arterial Disease (Pad)mentioning
confidence: 99%